Cardiovascular dysfunctions and sympathovagal imbalance in hypertension and prehypertension: physiological perspectives. (January 2013) - Pal, Gopal Krushna; Pal, Pravati; Nanda, Nivedita; Amudharaj, Dharmalingam; Adithan, Chandrasekaran
Hypertension (HTN) and prehypertension (pre-HTN) have been identified as independent risk factors for adverse cardiovascular events. Recently, increased psychosocial stress and work stress have contributed to the increased prevalence of HTN and pre-HTN, in addition to the contribution of obesity, diabetes, poor food habits and physical inactivity. Irrespective of the etiology, sympathetic overactivity has been recognized as the main pathophysiologic mechanism in the genesis of HTN and pre-HTN. Sympathovagal imbalance owing to sympathetic overactivity and vagal withdrawal is reported to be the basis of many clinical disorders. However, the role played by vagal withdrawal has been under-reported. In this review, we have analyzed the pathophysiologic involvement of sympathovagal imbalance in the development of HTN and pre-HTN, and the link of sympathovagal imbalance to cardiovascular dysfunctions. We have emphasized that adaptation to a healthier lifestyle will help improve sympathovagal homeostasis and prevent the occurrence of HTN and pre-HTN.